University Industry collaboration strengthens with 3 HB approach - Mimi Rabita, Abd Wahit (UMPSA, 2023)
KUANTAN, 27 November 2023 - Dato' Mohd Sharil Abdullah, the Director of the Industrial Relations Division at the Department of Higher Education, Ministry of Higher Education (KPT), outlined the '3 HB' approach to intensify efforts in identifying the future needs of universities and industries. This aligns with the requirements of the New Industrial Master Plan 2030 (IMP 2030).